Audit IT Process Po-01 to Academic Information Systemin Higher Education Polytechnic using the Cobit Framework - Rendra Trisyanto Surya; Syafrizal Ikram; Murhaban Murhaban (Jurnal Sosial Teknologi, 2022)
The role of information technology in higher education is to realize academic effectiveness. Academic Information System (SIAK) which is loaded with the use of Information Technology (IT). The PO1 IT Process Governance audit based on the COBIT standard, namely “Define a Strategic Information Technology Plan” then became a strategic issue for the success of higher education management, especially the SIAK Polytechnic campus which uses information technology-based tools in its teaching and learning process. This study aims to measure the level of IT Process PO-01 governance in relation to Academic Information Systems in Vocational Model High Schools (Polytechnics). The sample of this research is nine Vocational High Schools (Polytechnics) in Bandung. From the results of the study, it is known that the IT Process Governance PO-01 at SIAk Vocational Colleges is still at Level 2, namely "Repeatable but Intuitive". The effectiveness of governance is still determined by the competence of the individual or part of the personnel who carry out the IT Function (technical) and the assignment is ad-hoc. IT management at SIAk has not been internalized and refers to Best Practice. But on the other hand, it has begun to be seen that the Polytechnic management has a fairly good awareness of the importance of IT Governance and wants to make it an enabler for the Academic Information System (SIAk). However, there is still a fairly high gap between what is and what should be desired as in COBIT Best Practice.